2009
DOI: 10.1057/jphp.2009.40
|View full text |Cite
|
Sign up to set email alerts
|

Examining gender equity in health policies in a low- (Peru), middle- (Colombia), and high- (Canada) income country in the Americas

Abstract: Gender inequities in health prevail in most countries despite ongoing attempts to eliminate them. Assessment of gender-sensitive health policies can be used to identify country specific progress as well as gaps and issues that need to be addressed to meet health equity goals. This study selected and measured the existence of gender-sensitive health policies in a low- (Peru), middle- (Colombia), and high (Canada)-income country in the Americas. Investigators selected 10 of 20 gender-sensitive health policy indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…In developed countries, for example, Canada, efforts to promote gender equality in education and employment have been numerous [6], but many developing countries exhibit considerable gender inequality in education [7], employment [8], and health outcomes [9]. For example, there are large discrepancies in employment status between the sexes in black South African adults [8].…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, for example, Canada, efforts to promote gender equality in education and employment have been numerous [6], but many developing countries exhibit considerable gender inequality in education [7], employment [8], and health outcomes [9]. For example, there are large discrepancies in employment status between the sexes in black South African adults [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a U.S. survey of persons aged 18 and older by the National Institute of Mental Health (NIMH), women were 70% more likely to experience depression than men (4). A woman’s education level has also been associated with her use of health services beyond primary care (17). …”
Section: Introductionmentioning
confidence: 99%
“…In Canada, efforts to promote gender equality in education and employment have been numerous [3], but few studies have investigated the influence of such policies in populations. Canada ranked sixteenth worldwide on the United Nations' gender inequality index in 2008 [4], and several Canadian studies have shown important gender differences in chronic illness, distress, mental health, and self-rated health [5,6].…”
Section: Introductionmentioning
confidence: 99%